Occupational Mobility, Educational Mobility and Intergenerational Transmission of Disadvantages in Europe - Tomáš Želinský; Martina Mysíková; Jiří Večerník (Ekonomický časopis / Journal of Economics, 2016)
Empirical literature offers a number of studies suggesting that living conditions in childhood can significantly influence achievements and living conditions in adulthood. The aim of this paper is to answer the question: To what extent is the intergenerational transmission of poverty associated with social mobility (in terms of educational and occupational intergenerational mobility) in the European Union (and Iceland, Switzerland and Norway)? Our analyses are based on EU-SILC 2011, `Intergenerational transmission of disadvantages' module microdata. Interpretations of the findings are based on the ordered logit models estimated at European and country levels. The results suggest that both educational and occupational mobility are in a statistically significant positive relationship with the intergenerational transmission of poverty (proxied by a change in the perceived financial stress of the household).
Keywords: I31; I32; Z13; 330; intergenerational transmission of poverty; social mobility; Europe; EU-SILC